Teachers' Efforts to Overcome Barriers to Integrated Social Studies Learning at Junior High School - Novian Kharis; Beatrice A Namatsi; Walter Sengai (Indonesian Journal of Education Research (IJoER), 2023)
Purpose of the study: The purpose of this research is to find out what obstacles there are in Integrated Social Studies learning and to find out what efforts have been made by teachers to overcome barriers to learning Integrated Social Sciences. Methodology: The methodology used in this research is a qualitative method. The sampling technique used was purposive sampling, taking Integrated Social Sciences teachers and class 8A students at junior high school as data sources. Data was collected through passive observation by researchers and in-depth interviews. Main Findings: Research findings show that Integrated Social Studies learning at junior high school is considered boring by students because of the load of material presented by teachers and the lack of facilities and infrastructure, especially in terms of electronic media. Novelty/Originality of this study: This research contributes to the understanding of the obstacles and efforts made in Integrated Social Sciences learning. The results of this research can be a reference for related parties, such as schools and teachers, to overcome the problems faced in Integrated Social Sciences learning and improve the quality of learning.